A potential of iron slag-based soil amendment as a suppressor of greenhouse gas (CH4 and N2O) emissions in rice paddy - Galgo, Snowie Jane C.; Canatoy, Ronley C.; Lim, Ji Yeon; Park, Hyon Chol; Kim, Pil Joo (Frontiers in Environmental Science, 2024)
Iron slag-based silicate fertilizer (SF) has been utilized as a soil amendment in rice paddy fields for over 50 years. SF, which contains electron acceptors such as oxidized iron (Fe3+) compounds, is known to reduce methane (CH4) emissions, which have a global warming potential (GWP) of 23, higher than that of carbon dioxide (CO2). However, the dynamics of nitrous oxide (N2O), which has a GWP of 265, were questionable. Since the reduced Fe (Fe2+) can react as an electron donor, SF application might suppress N2O emissions by progressing N2O into nitrogen gas (N2) during the denitrification process. To verify the influence of SF application on two major greenhouse gas (GHG) dynamics during rice cultivation, three different kinds of SF were prepared by mixing iron rust (>99%, Fe2O3) as an electron acceptor with different ratios (0, 2.5, and 5%) and applied at the recommended level (1.5 Mg ha−1) for rice cultivation. SF application was effective in decreasing CH4 emissions in the earlier rice cropping season, and seasonal CH4 flux was more highly decreased with increasing the mixing ratio of iron rust from an average of 19% to 38%. Different from CH4 emissions, approximately 70% of seasonal N2O flux was released after drainage for rice harvesting. However, SF incorporation was very effective in decreasing N2O emissions by approximately 40% over the control. Reduced Fe2+ can be simultaneously oxidized into Fe3+ by releasing free electrons. The increased electron availability might develop more denitrification processes into N2 gas rather than NO and N2O and then decrease N2O emissions in the late rice cultivation season. We could find evidence of a more suppressed N2O flux by applying the electron acceptor-added SFs (SF2.5 and SF5.0) to a 49%–56% decrease over the control. The SF application was effective in increasing rice productivity, which showed a negative-quadratic response to the available silicate (SiO2) concentration in the soil at the harvesting stage. Grain yield was maximized at approximately 183 mg kg−1 of the available SiO2 concentration in the Korean rice paddy, with a 16% increase over no-SF application. Consequently, SF has an attractive potential as a soil amendment in rice paddy to decrease GHG emission impacts and increase rice productivity.